2017
DOI: 10.1007/s11940-017-0445-6
|View full text |Cite
|
Sign up to set email alerts
|

Advanced MRI Techniques in the Monitoring of Treatment of Gliomas

Abstract: With advances in treatments and survival of patients with glioblastoma (GBM), it has become apparent that conventional imaging sequences have significant limitations both in terms of assessing response to treatment and monitoring disease progression. Both 'pseudoprogression' after chemoradiation for newly diagnosed GBM and 'pseudoresponse' after anti-angiogenesis treatment for relapsed GBM are well-recognised radiological entities. This in turn has led to revision of response criteria away from the standard Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 77 publications
0
43
0
Order By: Relevance
“…A combination of the presented method with qMRI techniques measuring further parameters (DTI, CBV, T2, PD, perfusion) and more novel MRI techniques (diffusion kurtosis imaging, chemical exchange saturation transfer) might provide a more precise characterization of the area beyond the enhancing tumor and emerge as a useful tool for initial tumor characterization and for treatment monitoring …”
Section: Discussionmentioning
confidence: 99%
“…A combination of the presented method with qMRI techniques measuring further parameters (DTI, CBV, T2, PD, perfusion) and more novel MRI techniques (diffusion kurtosis imaging, chemical exchange saturation transfer) might provide a more precise characterization of the area beyond the enhancing tumor and emerge as a useful tool for initial tumor characterization and for treatment monitoring …”
Section: Discussionmentioning
confidence: 99%
“…MRS uses the proton signals to determine relative concentrations of target metabolites rather than an anatomical image. In various studies, MRS has been shown capable of identifying regions of tissue enriched with stem-like cell-enriched foci [131], detecting tumours with mutations in the isocitrate dehydrogenase (IDH) genes [132,133], and assessing response to various therapies such as radiation and PI3K/mTOR inhibitors [134,135]. Further, the use of hyperpolarized (HP) contrast agents can significantly increase the sensitivity of MRS by enhancing the signal-to-noise ratio [136,137].…”
Section: Medical Imaging and Histopathologymentioning
confidence: 99%
“…CEST creates imaging contrast based on sensitivity to chemical exchange of protons on functional metabolic groups rather than exogenously administered contrast. 23 The CEST technique which has primarily been applied to brain tumor imaging is the exchange of amide protons of endogenous tissue proteins and peptides, known as amide proton transfer (APT). Early studies have shown a potential use of APT in the differentiation of tumor from edema and true progression versus pseudoprogression, although these techniques have yet to be widely applied clinically.…”
Section: Advanced Mri Techniquesmentioning
confidence: 99%